ANALISIS IMPLEMENTASI PEMBELAJARAN BERBASIS STEM UNTUK MEMFASILITASI KEMAMPUAN PEMECAHAN MASALAH MATEMATIS DALAM ERA NEW NORMAL - Dwi Khoerunnisa; Almas Inka Amiroh; Nailatudz Dzakirah Nurshalihah; Finola Marta Putri (ALGORITMA: Journal of Mathematics Education, 2021)
In 2045, Indonesia hopes that it has achieved its goals, the welfare of the people is more advanced, developed, and excelled in various fields, one of which is education. STEM is a learning approach that incorporates four areas of expertise, namely science, technology, engineering, and mathematics, in problem-solving-based activities. STEM-based learning expects to be a solution to facilitate mathematical problem-solving skills in the New Normal era towards golden Indonesia 2045. This study analyzes mathematical problem-solving skills by implementing STEM-based learning in the New Normal era towards the golden Indonesia 2045. The method used is descriptive. The source of research data is secondary data. It was collecting data using a literature study. The research study stated that percentage of students' mathematical solving ability achievement increased after using STEM-based learning. It is appropriate to apply in the New Normal era. Students could solve problems in adapting to their lives which is one of the preparations for facing the golden age of 2045.  This study concludes that STEM-based learning can improve students' mathematical problem-solving abilities.